2003
DOI: 10.1101/gr.1299703
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Variation Analysis in 65 Candidate Genes for CNS Disorders in a Representative Sample of the European Population

Abstract: The detailed investigation of variation in functionally important regions of the human genome is expected to promote understanding of genetically complex diseases. We resequenced 65 candidate genes for CNS disorders in an average of 85 European individuals. The minor allele frequency (MAF), an indicator of weak purifying selection, was lowest in radical amino acid alterations, whereas similar MAF was observed for synonymous variants and conservative amino acid alterations. In noncoding sequences, variants loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
40
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 32 publications
(54 reference statements)
11
40
1
Order By: Relevance
“…As described earlier, 5 MAF differed significantly between synonymous SNPs (MAF ¼ 12.0%, n ¼ 143), conservative amino-acid alterations (MAF ¼ 8.3%, n ¼ 105) and radical amino-acid alterations (MAF ¼ 4.7%, n ¼ 26) (P ¼ 0.001, Kruskal-Wallis H test). When analyzing the 453 noncoding SNPs, we found MAF of SNPs located in regions annotated as highly conserved (either mouse or rat or both) (MAF ¼ 11.2%, n ¼ 119) significantly lower than MAF of noncoding SNPs not located in such highly conserved regions (MAF ¼ 14.0%, n ¼ 334) (P ¼ 0.001, two-sided Mann-Whitney U test).…”
Section: Characteristics Of Observed Single-nucleotide Polymorphismssupporting
confidence: 69%
See 4 more Smart Citations
“…As described earlier, 5 MAF differed significantly between synonymous SNPs (MAF ¼ 12.0%, n ¼ 143), conservative amino-acid alterations (MAF ¼ 8.3%, n ¼ 105) and radical amino-acid alterations (MAF ¼ 4.7%, n ¼ 26) (P ¼ 0.001, Kruskal-Wallis H test). When analyzing the 453 noncoding SNPs, we found MAF of SNPs located in regions annotated as highly conserved (either mouse or rat or both) (MAF ¼ 11.2%, n ¼ 119) significantly lower than MAF of noncoding SNPs not located in such highly conserved regions (MAF ¼ 14.0%, n ¼ 334) (P ¼ 0.001, two-sided Mann-Whitney U test).…”
Section: Characteristics Of Observed Single-nucleotide Polymorphismssupporting
confidence: 69%
“…Previous large-scale resequencing studies 4,5,8,9 found lower nucleotide diversity for coding regions compared to noncoding regions and decreased allele frequency for coding SNPs. These findings can be explained by the influence of purifying selection on nucleotide diversity in the human genome.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations